Low savings rates in the economic community of West African States (Ecowas): The role of the political instability-income interaction - Abu, Nurudeen; Abd Karim, Mohd Zaini; Azman Aziz, Mukhriz Izraf (Walter de Gruyter, 2014)
This paper employs PCSE, OLS and TSLS with random effects to investigate the impact of the political instabilityincome interaction on savings in ECOWAS countries during the period 1996-2012.The empirical evidence illustrates that higher political stability is associated with higher savings and income levels moderate the adverse effect of political instability on savings, indicating that the impact of political instability on savings is higher in low income ECOWAS countries, but lesser at higher levels of income. The paper recommends the promotion of political stability via increases in incomes to raise savings in the ECOWAS region.